Rerum Novarum: Um guia de leitura - Aquino Júnior, Francisco de (Revista Eclesiástica Brasileira, 2019)
A Encíclica Rerum Novarum tem uma importância muito grande no diálogo da Igreja com o mundo moderno e, sobretudo, no desenvolvimento práxico-teórico da dimensão social da fé. É um texto decisivo no processo de renovação eclesial que desembocou no Concílio Vaticano II e em sua recepção latino-americana. Mas não é um texto simples e fácil de entender como pode parecer à primeira vista. Daí a importância desse trabalho que, como indica seu subtítulo, pretende ser um guia de leitura da Encíclica. Começa indicando o contexto socioeclesial em que ela surge e ao qual procura responder. Faz uma apresentação panorâmica da sua estrutura e conteúdo fundamentais. E conclui destacando alguns pontos importantes para sua adequada compreensão e interpretação. Abstract: The Encyclical Rerum Novarum is extremely important for the dialogue between the Church and the modern world, and, in particular for the practical-theoretical development of the social dimension of the faith. It is a decisive text in the process of ecclesial renovation that had as result the Vatican II Council and the reception it had in Latin America. However, it is not a text as simple and easy to understand as it may seem at first sight. Hence the importance of this work that, as indicated by its subheading, intends to be a reading guide for the Encyclical. It begins by pointing to the socio-ecclesial context in which the Encyclical appears and to which it intends to be an answer. It gives a panoramic presentation of its basic structure and contents. And it concludes by emphasizing some important points for its adequate comprehension and interpretation. Keywords: Industrial Revolution; Working Class; Social Catholicism; Leo XIII; Social Encyclical.